DESCRIPTION OF FACTORS OF CONSOLIDATION IN ENSURING SOCIETY STABILITY (Scientific journal of the Fergana State University, 2024)
The article examines the theoretical and methodological foundations of consolidation factors in ensuring social stability, dialectical features of social consolidation factors, the necessity and prospects of consolidation in ensuring social stability. Consolidation factors in ensuring the stability of the society were also analyzed